Monitoring of Voltage and Load Current Integration of Solar Panels with Electric Grids Android-Based - Hendro Darmono; Koesmarijanto Koesmarijanto; Ferizal Rif'at Naufal (Jurnal Jaringan Telekomunikasi, 2022)
Energy has been a human need since ancient times which has been an indicator of prosperity. However, that doesn't mean there won't be problems. The longer the petroleum reserves are getting depleted, so sooner or later humans must make more use of non-fossil alternative energy. An example is solar energy whose availability will never run out. Therefore, the application of Solar Power Generation (PLTS) technology to utilize its energy potential. The goal of the project is to develop a system for integrating solar power with electrical grids that can track the voltage and current of the applied load. The PZEM004T sensor produces an accuracy of 99.4 percent on the voltage variable test, which compares favorably with the ACS712 current sensor's accuracy of 97.8 percent. The lowest light intensity measured in the current variable test is 24351 lux with an output voltage of 17.32V at the time range between 4-5 pm, and the highest is 103901 lux with an output voltage of 18.9V at the time range between 11-12 am. Accuracy is 98.5 percent with light loads and 99.2 percent when the charger is used. Relays' ability to switch between resources has been tested, and the results have met expectations.